استجابة الأم الأولية لملامسة وليدها بعد الولادة مباشرة - مصطفى, نسرين; علي, وعد (Latakia University Journal -Medical Sciences Series, 2018)
يعتبر التلامس الفوري جلد-جلد (Skin to Skin Contact (SSC)) بين الأم ورضيعها بعد الولادة مباشرةً إجراء هام يجب أن تتضمنه الرعاية المقدمة للأم يعود عليها وعلى وليدها بالعديد من الفوائد الصحية, وتشكل رغبة الأم وردود فعلها تجاهه العامل الحاسم في نجاح هذا الإجراء, لذلك هدفت الدراسة الحالية إلى تحري الاستجابة الأولية عند 200 سيدة بعد ولادتهن الطبيعية مباشرةً, تم اختيارهن بطريقة عشوائية بسيطة من مستشفى التوليد والأطفال الوطني باللاذقية, وجمعت البيانات باستخدام استبيان مطور لهذا لغرض. وقد أظهرت الدراسة أن ثلاثة أرباع الأمهات تقريباً وافقن على ملامسة أطفالهن بطريقة (SSC) وثلاثة أرباع الموافقات تقريباً فضَّلن حمله وهو مغطى, وكانت أعلى نسبة استجابة للموافقات على ملامسة أطفالهن بعد الولادة مباشرةً هي التعبير عن الفرح بالطفل ثم حضنه وتقبيله, بينما كانت النسبة الأعلى من غير الموافقات على ملامسة أطفالهن بعد الولادة مباشرةً ترفض لمس الطفل لأنهن كن يتألمن. وقد أوصت الدراسة بضرورة تحري رغبة كل أم في غرفة المخاض في حمل طفلها العاري أو الملفوف ببطانية بعد ولادته مباشرةً, وعدم إجبارهن على (SSC) الفوري بعد الولادة, وأوصت بإجراء دورات تثقيفية وتدريبية مستمرة لتزويد جميع القابلات والممرضات العاملات في غرف المخاض بمعلومات ومهارات حول تطبيق (SSC) لجميع الأمهات بعد الولادة مباشرةً, وعمل أبحاث إضافية حول معلومات الممرضات والقابلات عن أهمية إجراء (SSC) الفوري بعد الولادة مباشرةً للأمهات. Skin-to-skin contact (SSC) between the mother and her infant immediately post-delivery is an important procedure that must be included in the care given to mother and her infant many health benefits. The mother's desire and reaction towards (SSC) is the decisive factor in the success of this procedure, so the current study aimed to investigate the initial reaction of 200 women towards (SSC) immediately after their vaginal delivery were randomly selected from the obstetric hospital and national children in Lattakia, data were collected using a questionnaire developed for this purpose. The study showed that nearly three-quarters of mothers agreed to have contact with their children in (SSC) and nearly three-quarters of approvals preferred to be covered. The highest rate of response to approvals for contact with their children immediately after birth was the expression of joy in child and then hugging and kissing him. While the highest response of non-approvals for contact with their children immediately Post-Delivery refused to touch the child because they were suffering of pain. The study recommended that every mother in the labor room be investigated for carrying her naked child or swaddled with a blanket immediately after birth, not forcing them to immediately postpartum (SSC), the study recommended to continuing education and training sessions to provide all midwives and nurses working in the labor rooms with information and skills (SSC) for all mothers immediately Post-Delivery, and further research on nurse and midwife information on the importance of prompt (SSC) immediately Post-Delivery.